1 STRATEGI PEMBANGUNAN DAERAH TERTINGGAL DI KABUPATEN LAMPUNG BARAT - annisa alifa ramadhani (Jurnal Ekonomi Pembangunan, 2018)
This thesis focuses on selecting the best strategy for West Lampung district in developing its area, by using SWOT and AHP analysis approach. This study uses two questionnaire instruments, namely SWOT questionnaire and AHP questionnaire. The result of this research concludes that the development target that must be prioritized is to build the supporting infrastructure of agriculture to develop the leading commodity center area.